2022
DOI: 10.1002/jbt.23120
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves estrus disorder induced by bisphenol A through attenuating oxidative stress, autophagy, and apoptosis

Abstract: Bisphenol A (BPA), as a widely used plasticizer, is easily absorbed by animals and humans. It has certain toxic effects on various tissues, including liver, heart, kidney, testis, and ovary. The toxic effects of BPA on animal reproduction have aroused widespread concern, but its regulatory mechanism and antidote in female animals estrus cycle remain unclear. In this study, the results displayed that BPA destroyed the normal estrus cycle of mice through decreasing the levels of progesterone and estradiol. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Resveratrol treatment ameliorated aflatoxin B 1 ‐induced GC apoptosis, this effect was due to the regulation of AKT/PI3K signaling pathway (Zhou et al, 2019). Moreover, a recent study reported that the protective effect of resveratrol on bisphenol A‐induced apoptosis in mice ovaries and GCs, and showed that resveratrol inhibited the expression of cleaved caspase‐9, cleaved caspase‐3, and Bax, increased Bcl‐2 (Jiao et al, 2022). Procyanidin B2 was shown to increase expression of antiapoptotic micoRNA let‐7a to alleviate H 2 O 2 ‐induced upregulation by Fas and caspase‐3 in GCs (Zhang et al, 2019).…”
Section: Natural Products and Bioactive Ingredients Of Tcm Inhibit Ap...mentioning
confidence: 99%
“…Resveratrol treatment ameliorated aflatoxin B 1 ‐induced GC apoptosis, this effect was due to the regulation of AKT/PI3K signaling pathway (Zhou et al, 2019). Moreover, a recent study reported that the protective effect of resveratrol on bisphenol A‐induced apoptosis in mice ovaries and GCs, and showed that resveratrol inhibited the expression of cleaved caspase‐9, cleaved caspase‐3, and Bax, increased Bcl‐2 (Jiao et al, 2022). Procyanidin B2 was shown to increase expression of antiapoptotic micoRNA let‐7a to alleviate H 2 O 2 ‐induced upregulation by Fas and caspase‐3 in GCs (Zhang et al, 2019).…”
Section: Natural Products and Bioactive Ingredients Of Tcm Inhibit Ap...mentioning
confidence: 99%
“…For instance, Yong et al found that resveratrol attenuated the effects of malathion on inducing autophagy and apoptosis in granulosa cells [ 20 ]. Jiao et al found that resveratrol inhibited autophagy by reducing BPA-induced autophagic vesicle formation in granulosa cells [ 21 ]. However, resveratrol was also found to activate autophagy and mitochondrial biogenesis in oocytes and granulosa cell complexes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%